CONFLICT CONSUMPTION OF SALT LAND (QUALITATIVE DESCRIPTIVE STUDY IN SALT FARMERS DEMANDING RIGHTS TO LAND BY PT. SALT): KONFLIK PEREBUTAN LAHAN GARAM ( STUDI DESKRIPTIF KUALITATIF PADA MASAYARAKAT PETANI GARAM YANG MENUNTUT HAK ATAS LAHAN OLEH PT. GARAM ) - Diska Ariesta Fajriani (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
The conflict that was happened in a salt land had been taking place for many year ago and flipped again at july 2009. This matter was cocked by strunggle the land is a 1975 to the owner of the land. So, it cocked a conflict between two of side, its a happened between a salt farmer were united Al Jihad Foundation. Based from the result of this research concluded that the conflict happened between salt farmer not only happened unilaterally but its happened too between salt farmer in Pinggir Papas then caused cracked a connection kindsip sosial between the farmers. The problem is cocked distribution a land done with no wise by the defending the land. Is solving the problem have been done the way mediation meeting which involved many out sider, but until yhis moment this is not. Find an agreement from the side of salt farmer.